A Proposal for Developing the Performance of Intermediate Second-Grade Students in Science Tests in Trends in International Mathematics & Science Study (TIMSS) - Abdulrahman Alshaikh, Asma (Journal of Education and e-Learning Research, 2021)
This study aimed at identifying the reasons responsible for the low performance of the students of the second intermediate grade in science's tests in the Trends in International Mathematics and Science Study (TIMSS). It also intends to provide a proposal for developing the performance of the students of the second intermediate grade in science tests in TIMSS. The study adopts the descriptive methodology. To achieve the results of the study, a questionnaire was prepared to identify the reasons responsible for the low performance of the students of the second intermediate grade in science tests in TIMSS. It consisted of three-dimension i.e. course content, student, and teacher & teaching performance. The results of the study showed that the study sample members are agreed with a high degree of all items of the questionnaire. Considering these results, the study provided a proposal to develop the performance of the students of the second intermediate grade in science tests in TIMSS. The proposal also consists of the same dimensions i.e. course content, student and teacher & teaching performance. The study recommends benefiting from the proposal to develop the performance of students of the second intermediate grade in science tests in TIMSS. It also suggests conducting future studies aimed at comparing some variables related to science education and learning in advanced-performing countries and the Kingdom of Saudi Arabia.